Myricetin relieves LPS‐induced mastitis by inhibiting inflammatory response and repairing the blood–milk barrier. Issue 9 (11th February 2019) - Kan, Xingchi; Liu, Bingrun; Guo, Wenjin; Wei, Libin; Lin, Yuanqing; Guo, Yingcheng; Gong, Qian; Li, Yanwei; Xu, Dianwen; Cao, Yu; Huang, Bingxu; Dong, Aiwen; et al.
Abstract: Mastitis, an inflammation of mammary gland, is a serious disease that affects the health of dairy cows around the world. Myricetin, a flavonoid from Bayberry, has been reported to suppress various inflammatory response. The aim of this study was to evaluate the effect of myricetin on lipopolysaccharide (LPS)‐induced in vivo and in vitro mastitis model and clarify the underlying mechanism. In vivo experiments, myricetin attenuated the severity of inflammatory lesion and neutrophil infiltration. Moreover, myricetin pretreatment induced a significant decrease in the activity of myeloperoxidase (MPO) and the production of TNF‐α, IL‐6, and IL‐1β triggered by LPS. Myricetin pretreatment could also increase the integrity of the blood–milk barrier and upregulate the tight junction proteins in LPS‐induced mice mastitis. In vitro, myricetin inhibited LPS‐induced inflammatory response in mice mammary epithelial cells (mMECs). In the further mechanism studies, we found that the anti‐inflammatory effect of myricetin was mediated by inhibiting LPS‐induced phosphorylation of AKT, IKK‐α, IκB‐α, and P65 in vivo and in vitro. Collectively, these data suggested that myricetin effectively ameliorated the inflammatory response by inhibiting the AKT/IKK/NF‐κB signaling pathway and repairing the integrity of blood–milk barrier in LPS‐induced mice mastitis. Abstract : Myricetin administration significantly alleviates lipopolysaccharide (LPS)‐induced inflammatory response via inhibiting AKT/IKK/NF‐κB signaling pathway and repairing blood–milk barrier via upregulating the protein levels of claudin‐3, occludin, and ZO‐1 in LPS‐induce mice mastitis.